Legal Analysis of Notary's Obligations and Responsibilities in Providing Social Services in Medan City - Adnan, Muhammad Ali; Tarigan, Erlangga P Suranta; Zendrato, Rizaldo; Sunarto, Atika (Jurnal Daulat Hukum, 2025)
Notaries have important duties and responsibilities in providing social services, in accordance with Law No. 2/2014 on the amendment of Law No. 30/2004 on the Office of Notary. These duties are mainly related to making legal deeds and ensuring that legal actions are carried out in accordance with applicable rules. This study aims to examine the duties and responsibilities of notaries in social services as well as the impact of negligence in performing duties, including the legal sanctions that can be imposed. The analysis shows that notary negligence can harm the parties involved and undermine trust in the notary profession. Therefore, supervision of notary performance needs to be improved, and sanctions should be strictly applied to those who are negligent. Continuous education and training, as well as transparency in decision making, are important to reduce errors and improve the quality of legal services.